In vitro effects of hop pellets and oak extracts in combination on ruminal fermentation parameters - Van, Quynh Chau Dang; Gardin, Cécile; Mignolet, Éric; Froidmont, Éric; Focant, Michel; Larondelle, Yvan (Biotechnologie, agronomie, société et environnement, 2018)
Hop and oak extracts have been found to possess anti-methanogenic and protein-sparing effects in the rumen. An in vitro incubation with ruminal fluid was conducted to study the effects of increasing inclusions of hop pellets and oak extracts, alone or in combination, on ruminal fermentation parameters. The combination of hop pellets and oak extracts reduced total volatile fatty acid (VFA) production compared with the control (no additive), whereas these additives alone had no effect. The acetate/propionate ratio decreased with the combination of hop pellets and oak extracts, as compared to the control, whereas these additives alone had no effect. Hop pellets at the highest dose alone or in combination with oak extracts reduced the methane (CH4) production, as compared to the control. The CH4/VFA molar ratio was lower than the control for hop pellets at the highest dose combined with oak extracts, whereas the additives used alone had no effect. Ammonia N concentration was reduced by oak extracts treatments at the highest dose alone or in combination with hop pellets, as compared to the control. Hop pellets and oak extracts altered in vitro rumen fermentation with some responses being non-linear when used in combination.